"I am willing to do both well": Chinese academic mothers facing tension in family and career. - Bao, Li; Wang, Guanghua (Frontiers in psychology, 2022)
Academic mothers perform intersected roles. They carry out their profession in workplaces, while they take the "second shift" of motherhood back to their families. The contested expectations in family and career built by the heterosexual matrix cause tension to academic mothers. We qualitatively investigate the interview data of six Chinese women academics on how they perform to negotiate their motherhood and academic work in the context of Chinese higher education, driven by the Butlerian theoretical concept of the heterosexual matrix. The findings suggest that Chinese academic mothers play a zero-sum game between being mothers and being academics, deriving from their ontological responsibilities of motherhood. We conclude that in the masculine academia, these women academics help maintain the heterosexual matrix by satisfying the gender normativity when they negotiate their performances in their family and career; meanwhile, most have developed some strategies to achieve their career advancement.; Competing Interests: The authors declare that the research was conducted in the absence of any commercial or financial relationships that could be construed as a potential conflict of interest. (Copyright © 2022 Bao and Wang.)
Keywords: 2000 à aujourd'hui; 2020-2029; approches et analyses; asie; chine; conciliation famille-travail; famille; femmes* universitaires; hétérosexisme; maternité; matrice hétérosexuelle; projet charge mentale; périodes historiques; ressource en ligne; régions géographiques; sexisme; systèmes d'oppressions; thématiques; travail

“I have no room of my own”: COVID-19 pandemic and work-from-home through a gender lens - Chauhan, Priyanshi (Gender Issues, 2022)
Working from home is not gender neutral. As the COVID-19 pandemic has relocated all non-essential work to the home setting, it becomes imperative to examine the phenomenon through a gender lens. Accordingly, I conducted a qualitative study using semi-structured interviews with 30 dual-earning married couples in India to study the gendered work-from-home experiences of men and women during the pandemic. The findings suggest that the pandemic has disproportionately increased the burden of unpaid work for women as compared to men. Women are negotiating gendered time–space arrangements within their households with the allocation of limited resources being in favor of men. When this interacts with work, gender inequalities are reinforced both at work and home. Gender roles and unpaid work determine women’s choices regarding when and where to work, boundary management between work and non-work domains, and their experiences of social isolation. Further, gender roles have also affected women’s decisions regarding returning to work post-pandemic, where some women may not be returning to work at all. Finally, the paper identifies how gender intersects with the existing conceptual frameworks of working from home, and makes a strong case for integrating gender considerations in the work-from-home policies. © 2022, The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature.
Keywords: 2000 à aujourd'hui; 2020-2029; approches et analyses; asie; conciliation famille-travail; covid-19; famille; hétérosexisme; inde; inégalités; inégalités hommes-femmes; pandémie; projet charge mentale; périodes historiques; régions géographiques; systèmes d'oppressions; thématiques; travail; travail gratuit

‘Passionate aesthetics’: T-P gender practices and discourses, and the hierarchies within lesbian (lala) communities in contemporary mainland China - Wang, Yiran (Journal of Gender Studies, 2021)
En tant que couple masculin-féminin comparable aux genres lesbiens butch-femme dans les sociétés euro-américaines, les rôles de genre TP constituent des éléments vivants dans la sous-culture lesbienne, ou lala , de la Chine continentale contemporaine. Sur la base d'une étude ethnographique menée au milieu des années 2010 à Shanghai et dans la province du Yunnan, en Chine, et en appliquant le cadre théorique de « l'esthétique passionnée », j'étudie dans cet article les discours et les pratiques pertinents pour les genres TP . J’analyse comment les hiérarchies ont été (re)produites au sein des communautés lala et comment, dans ces processus, les compréhensions (hétéro)normatives du genre et de la sexualité sont devenues à la fois sources de connaissances et objets de critique. Je soutiens que des esthétiques passionnées multiples et concurrentes, y compris la forme dominante d'hétéronormativité en Chine et les connaissances mondialisées, voire occidentales, sur le genre et la sexualité, ont entraîné trois grands types de hiérarchie parmi les lalas : des hiérarchies entre les catégories TP , qui sont paradoxalement définies par la notion de « pureté » ; les hiérarchies dans les discours féministes et activistes LGBTQ, qui banalisent, voire font taire, les incarnations quotidiennes du TP ; et les hiérarchies entre masculinité et féminité, qui encouragent diverses pratiques de masculinité féminine tout en valorisant la masculinité plutôt que la féminité.
Keywords: 2000 à aujourd'hui; 2010-2019; anthropologie; approches et analyses; asie; chine; discipline; genre; hétérosexisme; identités LGBTQIA2+; personnes lesbiennes; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; systèmes d'oppressions